2013
DOI: 10.1590/s1020-49892013000400010
|View full text |Cite
|
Sign up to set email alerts
|

Autoavaliação da saúde por idosos brasileiros: revisão sistemática da literatura

Abstract: The heterogeneity of factors associated with a negative self-evaluation indicates that the health of older individuals is defined by determinants that fall within a broad view of health. The standardization of questions and answers for research on self-assessment of health in older people is recommended, since this information will produce knowledge and allow monitoring and comparison of results, and will therefore be useful in guiding decision-making regarding the formulation of health policies for Brazil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0
52

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 25 publications
5
68
0
52
Order By: Relevance
“…5 The fact that elderly individuals who live in developed countries report a better health status than those living in developing countries could be linked to socio-economic issues, which have previously been addressed in several selfassessment studies. 6,11,13,27 In these studies, better socio-economic conditions were associated with better self-assessments of health status.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…5 The fact that elderly individuals who live in developed countries report a better health status than those living in developing countries could be linked to socio-economic issues, which have previously been addressed in several selfassessment studies. 6,11,13,27 In these studies, better socio-economic conditions were associated with better self-assessments of health status.…”
Section: Discussionmentioning
confidence: 87%
“…3,15,16,22,27,32 A study of elderly individuals in São Paulo reported that the presence of four or more chronic diseases was positively associated with a negative self-assessment of health, in both men and women. 34 Considering certain morbidities, a study conducted by Pagotto et al 30 confirmed an association between a poor perception of health and the presence of diabetes mellitus and osteomuscular problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic literature review showed greater than 25% prevalence of poor self-rated health in elderly Brazilians in studies published in recent years 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This disparity could be partially explained by the absence of internationally standardized answers and their categorization 27,28 . Other issues may also explain the different prevalence rates: presence of diseases in the study groups, age of the study groups, information sources (selected interviewees versus third parties), different positioning of questions on the questionnaire, study design issues, and adjustments in the analysis.…”
Section: Discussionmentioning
confidence: 99%